Implikasi Perubahan Kerapatan Bangunan Dan Kerapatan Vegetasi Terhadap Ruang Terbuka Hijau (RTH) Di Kota Tangerang - Ratu Kusumasindy; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2022)
Tangerang City has an increasing population with an annual average of 1.87% between 2009-2019. Increased space requirements, leading to land function changes. The conversion of land use will change the built-up and the vegetation index will affect green open spaces. If it does not support properly, there will be less green open space in Tangerang City. The purpose of the research is to examine implied changes in the built-up and the vegetation index on green open space in Tangerang City. The analysis will be carried out by built-up index, and vegetation index carried out in 2009, 2014, 2019. The analysis is carried out to determine the distribution of the built-up and the vegetation index in the City of Tangerang, so that it can be seen which locations dominated by class distribution high and very high vegetation density. The density class is the assumption that represents green open space. Based on the analysis of the results, the green open space of Tangerang City is less than 30%. So, implications are related to the need for green open space in Tangerang City. The government has implemented the green open space development that has been carried out in the Tangerang City RTRW 2012-2032.